The Actin/Spectrin Membrane-Associated Periodic Skeleton in Neurons - Unsain, Nicolas; Stefani, Fernando D.; Cáceres, Alfredo (Frontiers in Synaptic Neuroscience, 2018)
Neurons are the most asymmetric cell types, with their axons commonly extending over lengths that are thousand times longer than the diameter of the cell soma. Fluorescence nanoscopy has recently unveiled that actin, spectrin and accompanying proteins form a membrane-associated periodic skeleton (MPS) that is ubiquitously present in mature axons from all neuronal types evaluated so far. The MPS is a regular supramolecular protein structure consisting of actin “rings” separated by spectrin tetramer “spacers”. Although the MPS is best organized in axons, it is also present in dendrites, dendritic spine necks and thin cellular extensions of non-neuronal cells such as oligodendrocytes and microglia. The unique organization of the actin/spectrin skeleton has raised the hypothesis that it might serve to support the extreme physical and structural conditions that axons must resist during the lifespan of an organism. Another plausible function of the MPS consists of membrane compartmentalization and subsequent organization of protein domains. This review focuses on what we know so far about the structure of the MPS in different neuronal subdomains, its dynamics and the emerging evidence of its impact in axonal biology.